The Dark Side of Bank Wholesale Funding - Ratnovski, Lev (IMF Working Papers; Working Paper ;, 2010)
Banks increasingly use short-term wholesale funds to supplement traditional retail deposits. Existing literature mainly points to the "bright side" of wholesale funding: sophisticated financiers can monitor banks, disciplining bad but refinancing good ones. This paper models a "dark side" of wholesale funding. In an environment with a costless but noisy public signal on bank project quality, short-term wholesale financiers have lower incentives to conduct costly monitoring, and instead may withdraw based on negative public signals, triggering inefficient liquidations. Comparative statics suggest that such distortions of incentives are smaller when public signals are less relevant and project liquidation costs are higher, e.g., when banks hold mostly relationship-based small business loans.